Gigantopteris Schenk ex Yabe in the Capitanian–Wuchiapingian (middle-late Permian) flora of central Shanxi in North China: Palaeobiogeographical and palaeoecological implications. (February 2016) - He, Xuezhi; Wang, Shijun; Wan, Mingli; Hilton, Jason; Wang, Jun
Highlights: First discovery of Gigantopteris from central North China. Palaeogeographic distribution of Gigantopteris enlarged to include central North China. Permian regional flora of Shanxi is typical of Cathaysian Flora. North China Block was seasonally dry during mid-late Permian times. Abstract: The concept of the Cathaysian Flora was originally based on fossils from the Permian of central Shanxi Province in North China but is now recognized to be valid for the flora of much of East Asia during the Carboniferous and Permian periods. Although Gigantopteris Schenck ex Yabe is characteristic and often distinctive of the Cathaysian Flora in general, it has previously not been recorded in Shanxi Province within the central part of the North China. Recent investigations on the Capitanian–Wuchiapingian (middle-late Permian) flora of the Taiyuan East Hill Coalfield in Shanxi have yielded well-preserved specimens of Gigantopteris dictyophylloides Gu and Zhi within the Upper Shihhotse Formation, contained within continental red-beds interpreted as representing a floodplain environment. Discovery of G. dictyophylloides extends the palaeogeographic distribution of the genus and shows that the Permian flora of Shanxi is more typical of the Cathaysian Flora than previously thought. Results also provide new information on the ecology of G . dictyophylloides based on assessments of its occurrence within depositional sedimentary facies from which we conclude that this species thrived in alluvial–fluvial sediments on the North China Block. We also conclude that the red beds of the Upper Shihhotse Formation that yield gigantopterids most likely formed under a seasonally dry climate rather than a vague statement that these red beds were formed generally under arid conditions as previously thought.